SUMOylation by the E3 ligase TbSIZ1/PIAS1 positively regulates VSG expression in Trypanosoma brucei. - Diana López-Farfán; Jean-Mathieu Bart; Domingo I Rojas-Barros; Miguel Navarro (PLoS Pathogens, 2014)
Bloodstream form trypanosomes avoid the host immune response by switching the expression of their surface proteins between Variant Surface Glycoproteins (VSG), only one of which is expressed at any given time. Monoallelic transcription of the telomeric VSG Expression Site (ES) by RNA polymerase I (RNA pol I) localizes to a unique nuclear body named the ESB. Most work has focused on silencing mechanisms of inactive VSG-ESs, but the mechanisms involved in transcriptional activation of a single VSG-ES remain largely unknown. Here, we identify a highly SUMOylated focus (HSF) in the nucleus of the bloodstream form that partially colocalizes with the ESB and the active VSG-ES locus. SUMOylation of chromatin-associated proteins was enriched along the active VSG-ES transcriptional unit, in contrast to silent VSG-ES or rDNA, suggesting that it is a distinct feature of VSG-ES monoallelic expression. In addition, sequences upstream of the active VSG-ES promoter were highly enriched in SUMOylated proteins. We identified TbSIZ1/PIAS1 as the SUMO E3 ligase responsible for SUMOylation in the active VSG-ES chromatin. Reduction of SUMO-conjugated proteins by TbSIZ1 knockdown decreased the recruitment of RNA pol I to the VSG-ES and the VSG-ES-derived transcripts. Furthermore, cells depleted of SUMO conjugated proteins by TbUBC9 and TbSUMO knockdown confirmed the positive function of SUMO for VSG-ES expression. In addition, the largest subunit of RNA pol I TbRPA1 was SUMOylated in a TbSIZ-dependent manner. Our results show a positive mechanism associated with active VSG-ES expression via post-translational modification, and indicate that chromatin SUMOylation plays an important role in the regulation of VSG-ES. Thus, protein SUMOylation is linked to active gene expression in this protozoan parasite that diverged early in evolution.